Tumor necrosis factor induces rapid down-regulation of TXNIP in human T cells - Levring, Trine B. (Sci Rep, 2019)
In addition to antigen-driven signals, T cells need co-stimulatory signals for robust activation. Several receptors, including members of the tumor necrosis factor receptor superfamily (TNFRSF), can deliver co-stimulatory signals to T cells. Thioredoxin interacting protein (TXNIP) is an important inhibitor of glucose uptake and cell proliferation, but it is unknown how TXNIP is regulated in T cells. The aim of this study was to determine expression levels and regulation of TXNIP in human T cells. We found that naïve T cells express high levels of TXNIP and that treatment of blood samples with TNF results in rapid down-regulation of TXNIP in the T cells. TNF-induced TXNIP down-regulation correlated with increased glucose uptake. Furthermore, we found that density gradient centrifugation (DGC) induced down-regulation of TXNIP. We demonstrate that DGC induced TNF production that paralleled the TXNIP down-regulation. Treatment of blood with toll-like receptor (TLR) ligands induced TNF production and TXNIP down-regulation, suggesting that damage-associated molecular patterns (DAMPs), such as endogenous TLR ligands, released during DGC play a role in DGC-induced TXNIP down-regulation. Finally, we demonstrate that TNF-induced TXNIP down-regulation is dependent on caspase activity and is caused by caspase-mediated cleavage of TXNIP.